Land Acquisition for Public Interest Development: Legal and Regulatory Perspectives in Indonesia - Yasim, Sulastri; Pratiwi, Andi Dewi; Nuraliah, Dewi; Mausili, Dwi Rianisa (Kirana Publisher (KNPub), 2025)
Land acquisition for public interest development in Indonesia is rife with conflicts and challenges, both in legal, social, and economic aspects. This research aims to analyze the implementation of the law in the land acquisition process, focusing on aspects of transparency, justice, and dispute resolution.The research employs a qualitative approach with a normative juridical method.It analyzes land acquisition for public interest development in Indonesia. The results indicate that while the law offers a robust legal foundation to safeguard landowners' rights, its implementation is marred by deficiencies, including insufficient socialization, the presence of land mafia, inconsistencies in land valuation, and protracted dispute resolution processes.This study underscores the imperative for enhanced coordination among government agencies, fortified supervisory mechanisms, and enhanced protection for affected communities to optimize the efficacy and fairness of the land acquisition process. In conclusion, the findings of this study offer a series of recommendations to enhance the efficacy of implementing the Land Acquisition Law, thereby facilitating the realization of equitable development objectives.